Rethinking progress: harmonizing the discourse on genetically modified crops - Bekele-Alemu, Abreham; Dessalegn-Hora, Obssi; Safawo-Jarso, Tura; Ligaba-Osena, Ayalew (Frontiers in Plant Science, 2025)
Genetically modified crops (GM crops) also known as biotech crops are crops that have been altered through genetic engineering techniques and under cultivation for approximately 28 years. By October 2024, over 30 nations have approved the cultivation of GM crops. The global area utilized for biotech crop production has reached 206.3 million hectares. Despite the substantial growth in the cultivation of these crops, debate continues between proponents and opponents of GM crops. In this article, critical concerns and common ground between the arguments of both sides were described. The main issues addressed include the naturalness of GM crops, religious perspectives, beneficial aspects, safety issues, socio-economic impacts and intellectual property rights. We argue that the classification GM crops as unnatural is a claim that lacks scientific reality. In a similar vein, comparing GM technology to the act of playing God is inappropriate. Moreover, the belief that GM crops do not contribute to yield improvements is inconsistent with empirical evidence. Additionally, the claim that foods produced from GM crops are unsafe for human consumption holds unseen concerns that is not on the ground. We have also highlighted the necessity of implementing intellectual property rights that support seed developers for a limited duration without violating farmers’ rights. In conclusion, as a consumer has the right to know what they eat, labeling of GM food products fosters transparency and enhance consumer autonomy.